IL-37 As a Potential Biotherapeutics of Inflammatory Diseases - Bai, Junhui; Li, Yukun; Li, Meixiang; Tan, Sijie; Wu, Daichao (Current Drug Targets, 2020)
Interleukin-37 (IL-37) was discovered as a new member of pro-inflammatory IL-1 superfamily. However, further studies suggested that IL-37 plays a critical anti-inflammatory role in innate and adaptive immunity. IL-37 may suppress the inflammatory process via intracellular SMAD family member 3 (SMAD3) and extracellular IL-18 Receptor alpha (IL-18Rα) signaling pathway, respectively. Meanwhile, the abnormal expression of IL-37 was observed in immune-mediated inflammatory diseases, such as inflammatory bowel disease, rheumatoid arthritis, atherosclerosis, systemic lupus erythematosus, asthma, and multiple sclerosis, which suggest IL-37 is a potential therapeutic target for these diseases. In this review, we summarize the anti-inflammatory mechanism of IL-37 and discuss the critical roles of IL-37 in the pathogenesis of these diseases. Further studies are required to confirm the effectiveness of IL-37 as a novel target for these inflammatory diseases.
Keywords: cytokine